2015
DOI: 10.1063/1.4906946
|View full text |Cite
|
Sign up to set email alerts
|

Optical and magneto-optical properties of Au:Conanoparticles and Co:Aunanoparticles doped magnetoplasmonic systems

Abstract: Size mediated control of the optical and magneto-optical properties of Co nanoparticles in Zr O 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Up to now, there was only a limited experimental works on the CMP thin films. 11,[13][14][15][16][17] For example, Yang et al studied the composite film of Co and Au with different Co:Au composition ratios and fabrication temperatures, where they noticed that the MO activities increased with increasing Co composition. 11 A recent study by David et al showed an improvement in magneto-optical surface plasmon resonance (MOSPR) responses and signal-to-noise ratio in a MOSPR sensor using a layer of Au-Co alloy instead of a single layer of Au or a tri-layer sandwiched Au/Co/Au structure.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, there was only a limited experimental works on the CMP thin films. 11,[13][14][15][16][17] For example, Yang et al studied the composite film of Co and Au with different Co:Au composition ratios and fabrication temperatures, where they noticed that the MO activities increased with increasing Co composition. 11 A recent study by David et al showed an improvement in magneto-optical surface plasmon resonance (MOSPR) responses and signal-to-noise ratio in a MOSPR sensor using a layer of Au-Co alloy instead of a single layer of Au or a tri-layer sandwiched Au/Co/Au structure.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the subsystem of Co clusters formed in Co x C 60 films with x>2 suggests their hidden potential in plasmonics, proper implementation of which could open new sources for spin current manipulation [17]. In spite of the enhanced damping of plasmonic excitations in the ferromagnetic metals [18,19], the plasmonic properties of the magnetic nanostructures are of highest interest due to the practical importance of the magneto-plasmonic effects detected in such nanomaterials [20][21][22][23][24]. The plasmon damping is usually overcome through fabrication of core-shell nanoparticles (magnetic metal−noble metal) [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Such materials can significantly change electronic, photonic, magnetic, mechanical and chemical properties of the surface, for example by inhibiting agglomeration or by imparting antiseptic properties [56]. In addition, systems "NSs + inorganic coatings" are promising for application in the field of catalysis, detection (for example, using SERS), creating of nano-and microelectronics elements [57].…”
Section: 3surface Coatingmentioning
confidence: 99%